2017
DOI: 10.3892/etm.2017.4596
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-32 promotes lipid accumulation through inhibition of cholesterol efflux

Abstract: Abstract. Interleukin-32 (IL-32) is a pro-inflammatory cytokine and its effects in various inflammatory diseases have been investigated. However, the role of IL-32 on atherosclerosis, an inflammatory disease, remains unknown. The present study examined the use of IL-32α, the most abundant transcript of IL-32, in the treatment of oxidized low-density lipoprotein (ox-LDL)-stimulated THP-1 macrophages for 24 h, which simulates a foam cell formation model. The effect of IL-32α (20, 50 and 100 ng/ml) on lipid depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Nevertheless, it remains to be established whether the proinflammatory response can be considered as a trigger of foam cells formation [29]. A couple of recent papers report that the proinflammatory response is promoted by intracellular lipid accumulation [30,31].…”
Section: Foam Cells In Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it remains to be established whether the proinflammatory response can be considered as a trigger of foam cells formation [29]. A couple of recent papers report that the proinflammatory response is promoted by intracellular lipid accumulation [30,31].…”
Section: Foam Cells In Atherosclerosismentioning
confidence: 99%
“…Liu et al in 2018 demonstrated that IL-34 can act as a promotor of the lipid accumulation in bone marrow-derived macrophages through the up-regulation of CD36 expression [30]. Earlier, Xu et al showed that IL-32 stimulated lipid accumulation in THP-1 macrophages and inhibited the cholesterol efflux, thus facilitating foam cell formation [31]. In addition, our recent data indicate that inflammatory cytokines not only promoted the accumulation of intracellular cholesterol caused by modified LDL, but were also able to induce cholesterol accumulation in cultured primary macrophages (Table 2).…”
Section: Proinflammatory Response As An Inductor Of Intracellular Lipmentioning
confidence: 99%
“…Up-regulated phagocytosis, in turn, leads to the increased production of pro-inflammatory cytokines that attract monocytes and other immune cells to the emerging site of atherosclerotic lesion. Different research groups have shown that pro-inflammatory cytokines promote intracellular lipid accumulation induced by atherogenic modified LDL [33][34][35][36][37]. Moreover, in some cases, intracellular lipid accumulation is induced under inflammatory conditions even when modified LDL is not present [37].…”
Section: Cellular Mechanisms Of Atherogenesismentioning
confidence: 99%
“…In vitro and in vivo studies disclosed that ABCA1 functions as an anti-inflammatory receptor and suppresses the expression of inflammatory factors such as interleukin-1beta, interleukin-6 and tumour necrosis factor-alpha and as an activator to stimulate the expression of anti-inflammatory factors such as IL-10 9 28. On the other hand, inflammatory factors also affect the expression of ABCA1 , for example, IL-32 has been shown to inhibit the expression of ABCA1 29…”
Section: Discussionmentioning
confidence: 99%